Global actions of nicotine on the striatal microcircuit - Plata, Victor E.; Duhne, Mariana; Pérez-Ortega, Jesús E.; Hernandez-Martinez, Ricardo; Rueda Orozco, Pavel E.; Galarraga, Elvira; Drucker-Colin, Rene; Bargas, Jose (Frontiers in Systems Neuroscience, 2013)
The question to solve in the present work is: what is the predominant action induced by the activation of cholinergic-nicotinic receptors (nAChrs) in the striatal network given that nAChrs are expressed by several elements of the circuit: cortical terminals, dopamine terminals, and various striatal GABAergic interneurons. To answer this question some type of multicellular recording has to be used without losing single cell resolution. Here, we used calcium imaging and nicotine. It is known that in the presence of low micromolar N-Methyl-D-aspartate (NMDA), the striatal microcircuit exhibits neuronal activity consisting in the spontaneous synchronization of different neuron pools that interchange their activity following determined sequences. The striatal circuit also exhibits profuse spontaneous activity in pathological states (without NMDA) such as dopamine depletion. However, in this case, most pathological activity is mostly generated by the same neuron pool. Here, we show that both types of activity are inhibited during the application of nicotine. Nicotine actions were blocked by mecamylamine, a non specific antagonist of nAChrs. Interestingly, inhibitory actions of nicotine were also blocked by the GABAA-receptor antagonist bicuculline, in which case, the actions of nicotine on the circuit became excitatory and facilitated neuronal synchronization. We conclude that the predominant action of nicotine in the striatal microcircuit is indirect, via the activation of networks of inhibitory interneurons. This action inhibits striatal pathological activity in early Parkinsonian animals almost as potently as L-DOPA.